Solid electrolyte, preparation method and use thereof
Through ultrasonic assisted in situ curing method, polymerization is induced at room temperature, and the problems of uneven heat conduction and large energy consumption of radiation polymerization in situ curing are solved, and more uniform solid electrolyte preparation and better battery performance are achieved, which is suitable for industrialization application.
Patent Information
- Application Number
- CN202410051317.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-12
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-01-12
AI Technical Summary
The preparation of solid electrolytes in situ curing has adverse effects on the material due to uneven thermal conductivity and high temperatures. Irradiation polymerization consumes a lot of energy and is unfavorable to the stability of the material, resulting in poor battery performance.
Ultrasonic assisted in situ curing method is used to induce initiator molecules to rupture under ultrasonic action to generate free radicals, realize controllable monomer polymerization and curing, avoid high temperature and high energy radiation, and prepare a uniform solid electrolyte.
Achieve more uniform solid electrolyte preparation at room temperature or lower temperatures, improve battery performance, reduce interface impedance, improve cycle performance and Coulomb efficiency, and the process is compatible with the existing liquid battery production process and is easy to industrialize.
Smart Images

Figure CN117855598B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid electrolytes, and in particular relates to a method for preparing a solid electrolyte, a solid electrolyte prepared by the preparation method, and also relates to the use of the solid electrolyte in a secondary battery. Background Art
[0002] Solid-state batteries usually refer to secondary batteries that use solid electrolytes. Compared with the liquid electrolytes used in traditional secondary batteries, the introduction of solid electrolytes can greatly improve battery safety performance and is more suitable for matching high-energy-density positive and negative electrodes to increase battery energy density.
[0003] In-situ curing is a solid-state battery preparation method with a relatively promising development prospect. This method usually involves mixing polymer monomers, electrolyte salts, initiators, additives, etc. into a precursor solution, and then injecting the precursor solution into the battery; after the precursor solution fully wets the electrode, most of the pores in the electrode are filled with the precursor solution, and under certain conditions (such as heating treatment or high-energy ray irradiation, etc.), the precursor solution is in-situ polymerized and cured inside the battery, and the precursor solution becomes solid, and a tight interface is formed between the electrode and the electrolyte, thereby making a solid polymer electrolyte and a solid-state battery. The in-situ curing process is fully compatible with the existing liquid battery manufacturing process, and the industrialization cost is low. For example, the Chinese patent application with publication number CN111533851A discloses the use of small molecule carbonates containing carbon-carbon double bonds, ethylene glycol acrylate, and initiators mixed and injected into the electrode-electrolyte interface of the solid-state battery, and thermally induced polymerization to form an electrode-electrolyte integrated all-solid-state battery. The Chinese patent application with publication number CN108493486A discloses the use of acrylates and initiators dissolved in electrolytes, injected into the interior of the battery, and initiating the polymerization of unsaturated double bonds under heating conditions to form an integrated gel polymer battery. The Chinese patent application with publication number CN105914405A discloses a method of injecting liquid epoxy compounds and lithium salts into the interior of the battery, initiating in-situ ring-opening curing under heating conditions to form an integrated all-solid polymer battery. The Chinese patent application with publication number CN106374139A discloses a method of using gamma rays or electron beams to initiate monomer polymerization / cross-linking to prepare a gel quasi-solid electrolyte and a corresponding quasi-solid-state battery. The unique advantage of these in-situ curing technologies is that the interface geometry matching between the electrolyte and the electrode is retained after curing, so the interface impedance is low and the battery performance is better.
[0004] However, the current in-situ solidification method for preparing solid electrolytes also has certain defects: (1) Thermal polymerization curing has the problem of uneven heat conduction rate inside the battery in large-scale battery production, which will lead to uneven polymerization rate and degree inside the battery, affecting the uniformity of the solid electrolyte and thus having an adverse effect on battery performance; at the same time, high temperature heating will also have an adverse effect on materials such as electrolyte salts inside the battery, such as the main salt LiPF in lithium batteries. 6 It is easy to decompose at high temperature, which will lead to the deterioration of battery performance. (2) For radiation polymerization curing, the commonly used ultraviolet light cannot penetrate the battery shell, and high-energy rays such as gamma rays are required to penetrate the battery steel shell, aluminum shell, aluminum plastic film, etc. for radiation polymerization. Not only does it consume a lot of energy, but high-energy ray irradiation will also have a certain adverse effect on the stability of battery materials. Summary of the invention
[0005] In view of this, the present invention proposes a method for preparing a solid electrolyte based on ultrasound-assisted in-situ curing. Ultrasonic-assisted in-situ curing refers to inducing or accelerating the rupture or decomposition of initiator molecules to produce free radicals under the action of ultrasound, thereby initiating the controlled free radical polymerization and curing of monomers in the precursor solution. High-energy ultrasound will cause cavitation in the solution, and the cavitation will break up the initiator molecules to form free radicals. The greater the pressure and temperature generated when the cavitation bubble ruptures, the higher the yield of free radicals. Compared with thermally initiated free radical polymerization curing, ultrasound-assisted in-situ curing can produce free radicals at room temperature or lower temperatures, while achieving more uniform solid electrolyte preparation and better battery performance. Based on the above mechanism, the preparation method of the present invention is proposed.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The present invention provides a method for preparing a solid electrolyte, comprising the following steps:
[0008] Providing a prepolymer precursor solution, wherein the prepolymer precursor solution contains a polymerizable monomer, an electrolyte salt and an initiator;
[0009] Providing a porous support material so that it is completely infiltrated by the prepolymer precursor liquid;
[0010] The impregnated porous support material is placed between the positive electrode sheet and the negative electrode sheet, and the polymerizable monomer is polymerized and solidified to form a solid electrolyte through ultrasonic induction.
[0011] In a further embodiment, the polymerizable monomer is a free radical polymerizable monomer.
[0012] In a further embodiment, the free radical polymerizable monomer is selected from at least one of methyl methacrylate, ethyl methacrylate, ethoxylated trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, glycidyl methacrylate, vinylene carbonate, and an oligomer monomer having a weight average molecular weight not exceeding 2000.
[0013] In a further embodiment, the oligomer monomer is selected from at least one of polyethylene glycol acrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, and polyethylene glycol methyl ether acrylate.
[0014] In a further embodiment, the electrolyte salt is a lithium salt or a sodium salt.
[0015] In a further embodiment, the lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorooxalatoborate, and lithium bis(oxalate)borate.
[0016] In a further embodiment, the sodium salt is at least one selected from sodium hexafluorophosphate, sodium tetrafluoroborate, sodium perchlorate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethylsulfonyl)imide, sodium trifluoromethanesulfonate, sodium difluorooxalatoborate, and sodium bis(oxalyl)borate.
[0017] In a further embodiment, the total molar concentration of the electrolyte salt in the prepolymer precursor solution is 0.5 to 4.0 mol / L.
[0018] In a further embodiment, based on the prepolymer precursor solution, the mass fraction of the initiator is 0.05 to 5 wt %.
[0019] In a further embodiment, the initiator includes at least one of azobisisobutyronitrile, azobisisoheptylnitrile, dimethyl azobisisobutyrate, dibenzoyl peroxide, lauroyl peroxide, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, tert-butyl benzoyl peroxide, methyl ethyl ketone peroxide, cyclohexanone peroxide, di-tert-butyl peroxide, and diisopropylbenzene peroxide.
[0020] In a further embodiment, the porous supporting material is selected from one or a composite of two or more of polyolefin membranes, ceramic-coated polyolefin membranes, PVDF-coated polyolefin membranes, polyimide membranes, polyethylene terephthalate membranes, cellulose nonwoven membranes, and glass fiber membranes.
[0021] In a further embodiment, the prepolymer precursor solution also contains a plasticizer additive.
[0022] In a further embodiment, the plasticizer additive is selected from at least one of fluoroethylene carbonate, ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, vinylene carbonate, succinonitrile, glutaronitrile, ionic liquid, and inorganic solid electrolyte powder.
[0023] In a further embodiment, based on the prepolymer precursor solution, the mass fraction of the plasticizer additive is 0.5 to 80 wt %.
[0024] In a further embodiment, the reaction temperature of the ultrasonic induced polymerization is 20-50° C., the ultrasonic power is 100 W-1000 W, the ultrasonic frequency is 20 kHz-80 kHz, and the ultrasonic time is 0.5 h-24 h.
[0025] The present invention further provides a solid electrolyte, which is prepared by the above-mentioned preparation method.
[0026] The present invention further provides a solid-state secondary battery, which contains the solid electrolyte prepared by the preparation method as described above.
[0027] In a further embodiment, the solid-state secondary battery is a solid-state lithium secondary battery or a solid-state sodium secondary battery.
[0028] In a further embodiment, the solid-state lithium secondary battery is a lithium ion battery or a lithium metal battery.
[0029] In a further embodiment, the solid-state sodium secondary battery is a sodium ion battery or a sodium metal battery.
[0030] Beneficial effects of the present invention:
[0031] The solid electrolyte preparation method in the present invention belongs to ultrasound-assisted in-situ curing, which is to inject the prepolymer precursor into the battery, so that it is initiated and polymerized under high-frequency ultrasound to form a uniform solid electrolyte from all parts of the battery, and an integrated solid-state battery is formed at the same time. There is a close interface contact between the solid electrolyte and the solid electrode in the solid-state battery, so it can alleviate the problems of uneven internal volume change of the battery due to different polymerization rates and poor battery performance caused by inconsistent polymer crystallinity. Compared with thermally initiated free radical polymerization curing, ultrasound-assisted in-situ curing can produce free radicals at room temperature or at a lower temperature, which helps to achieve more uniform solid electrolyte preparation and better battery performance. The ultrasonic in-situ polymerization method for preparing solid electrolytes in the present invention has significant advantages, can significantly improve the interface contact of solid-state batteries, effectively reduce impedance, and improve battery cycle performance and coulomb efficiency. At the same time, the present invention is technically feasible, can utilize the existing liquid battery production process, does not need to increase equipment investment, has good application prospects, and is easy to realize industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic diagram of the preparation of ultrasonic in-situ polymerization in a preferred embodiment of the present invention.
[0033] Figure 2 The Na||Na assembled in Example 1 and Comparative Example 1 of the present invention 3 V 2 (PO 4 ) 3 Comparison of electrochemical impedance spectroscopy of batteries.
[0034] Figure 3 is the Na||Na prepared in Example 1 of the present invention 3 V 2 (PO 4 ) 3 Typical charge and discharge curves of a solid-state battery.
[0035] Figure 4 is the Na||Na prepared in Example 1 of the present invention 3 V 2 (PO 4 ) 3 Cycle curve and Coulomb efficiency curve of solid-state battery. DETAILED DESCRIPTION
[0036] Embodiments of the present invention are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0038] The first aspect of the present invention discloses a method for preparing a solid electrolyte, which is achieved through ultrasonic in-situ polymerization. Different from traditional solid electrolyte polymerization methods (such as thermal polymerization, radiation polymerization, etc.), the preparation method uses ultrasonic induction to achieve uniform polymerization of the prepolymer precursor liquid inside the battery, thereby obtaining a solid electrolyte with tight solid-solid interface contact, good uniformity, and low interface impedance, further improving the electrochemical performance of the solid-state battery.
[0039] The main steps of the preparation method are as follows:
[0040] S1. Preparation of prepolymer precursor solution
[0041] The prepolymer precursor solution described herein is the conventional definition in the art, that is, it contains polymerizable monomers, electrolyte salts and initiators necessary for polymerization and curing to form a solid electrolyte.
[0042] The polymerizable monomer described herein refers to a free radical polymerizable monomer polymerized by free radical polymerization. In some specific embodiments of the present invention, the free radical polymerizable monomer is specifically exemplified by methyl methacrylate, ethyl methacrylate, ethoxylated trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, glycidyl methacrylate, vinylene carbonate, and at least one of an oligomer monomer having a weight average molecular weight not exceeding 2000, wherein the oligomer monomer is selected from at least one of polyethylene glycol acrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, and polyethylene glycol methyl ether acrylate, but is not limited thereto. In the prepolymer precursor solution, the amount of the polymerizable monomer is adjusted according to actual needs, and in some specific embodiments of the present invention, it is between 2wt% and 80wt%.
[0043] The electrolyte salt described herein is a conventional definition in the art, and its specific type can be selected according to the type of solid-state battery to be prepared. In some embodiments of the present invention, the electrolyte salt is a lithium salt or a sodium salt, wherein the lithium salt may be mentioned as an example of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethylsulfonyl imide, lithium trifluoromethanesulfonate, lithium difluorooxalate borate, and lithium bisoxalate borate. Examples of the sodium salt may be mentioned as sodium hexafluorophosphate, sodium tetrafluoroborate, sodium perchlorate, sodium bisfluorosulfonyl imide, sodium bistrifluoromethylsulfonyl imide, sodium trifluoromethanesulfonate, sodium difluorooxalate borate, and sodium bisoxalate borate, but are not limited thereto. It is understood that the concentration of the electrolyte can be adjusted as needed. In some specific embodiments of the present invention, its concentration is 0.5 to 4.0 mol / L, preferably, the concentration is 0.5 to 2.0 mol / L.
[0044] The initiator described herein is not particularly limited, and is any initiator in the art that can generate free radicals under the action of ultrasound. Specific examples include but are not limited to azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, dibenzoyl peroxide, lauroyl peroxide, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, tert-butyl peroxide benzoyl, methyl ethyl ketone peroxide, cyclohexanone peroxide, di-tert-butyl peroxide, and at least one of diisopropylbenzene peroxide. It is understood that the amount of the initiator can be adjusted according to the amount of the polymerizable monomer, based on the ability to achieve complete reaction of the polymerizable monomer. In some specific embodiments of the present invention, the mass fraction of the initiator is 0.05 to 5wt% based on the prepolymer precursor solution.
[0045] Further, as a preferred solution, some plasticizing additives can be added as needed in the prepolymer precursor solution to further improve the performance of the solid electrolyte. In the present invention, its kind is not particularly limited, and can be a conventional selection in this area, and the specific example that can be mentioned includes but is not limited to at least one of fluoroethylene carbonate, ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, vinylene carbonate, succinonitrile, glutaronitrile, ionic liquid, and inorganic solid electrolyte powder. In addition, it is understandable that the addition of plasticizing additives is not particularly limited, and can be adjusted as needed. According to the experience in this area, in some specific embodiments of the present invention, the mass fraction of the plasticizing additive added in the prepolymer precursor solution is 0.5~80wt%.
[0046] It is understood that the preparation of the prepolymer precursor solution only requires fully mixing the polymerizable monomer, electrolyte salt, initiator, etc. under anaerobic conditions. The anaerobic conditions may be under nitrogen protection or under the protection of a rare gas (such as argon, etc.).
[0047] S2. Use the prepolymer precursor to completely wet the porous support material
[0048] The porous support material described in this article refers to any membrane conventionally used in the preparation of solid electrolytes. Its specific type is not particularly limited. It can be a polyolefin membrane, such as a polyethylene membrane, a polypropylene membrane, and a multilayer polyolefin composite membrane; it can also be a ceramic-coated polyolefin membrane, a PVDF-coated polyolefin membrane, a polyimide membrane, a polyethylene terephthalate membrane, a cellulose non-woven membrane, and a glass fiber membrane. One or a composite of more than two.
[0049] The method of using the prepolymer precursor to completely infiltrate the porous support material can be to inject the prepolymer precursor into the battery when assembling the battery, so that the prepolymer precursor infiltrates the entire battery (including the porous support material, the positive electrode sheet, and the negative electrode sheet); it can also be directly dipping the porous support material into the prepolymer precursor to completely infiltrate it; it can also be dripping a sufficient amount of the prepolymer precursor on both sides of the porous support material to completely infiltrate it. The sufficient amount described here refers to the porous support material being completely infiltrated by the prepolymer precursor as a benchmark, and the specific amount can be adjusted according to actual needs (such as the size and thickness of the porous support material). In some specific embodiments of the present invention, the amount of the prepolymer precursor dripped on both sides of the porous support material is 40-80μl, such as 40μl, 60μl or 80μl. By completely infiltrating the porous support material with the prepolymer precursor, a close interface contact can be formed between the solid electrode and the solid electrolyte.
[0050] S3. Preparation of solid electrolyte
[0051] Specifically, the porous support material that has been completely soaked in step S2 is placed between the positive electrode sheet and the negative electrode sheet, and under ultrasonic induction, a free radical polymerization reaction of the polymerizable monomer is initiated to form a solid electrolyte. It can be understood that while forming the solid electrolyte, a solid-state battery is also prepared.
[0052] In the present invention, the polymerization of the prepolymer precursor solution inside the battery can be achieved by setting appropriate ultrasonic frequency, power and time, and the parameters can be adjusted according to the types of polymerizable monomers, initiators, etc. In some specific embodiments of the present invention, the ultrasonic-induced reaction temperature is 20°C to 50°C, the ultrasonic power is 100W to 1000W, the ultrasonic frequency is 20kHz to 80kHz, and the ultrasonic time is 0.5h to 24h. And the polymerization rate can be changed by adjusting the reaction temperature and ultrasonic power. Figure 1 A schematic diagram of ultrasound-induced polymerization to form a solid electrolyte is shown in FIG. 1 , where the assembled battery is placed in an ultrasonic instrument with an insulating liquid (such as ethanol or glycerol) as the medium.
[0053] The second aspect of the present invention provides a solid electrolyte, which is prepared by the preparation method described in the first aspect of the present invention.
[0054] The third aspect of the present invention discloses a solid-state secondary battery, which contains a solid electrolyte prepared by the preparation method described in the first aspect of the present invention. The solid-state secondary battery can be a solid-state lithium secondary battery or a solid-state sodium secondary battery. Further, it can be one of a lithium ion battery, a lithium metal battery, a sodium ion battery, and a sodium metal battery. It is understandable that the other components of the solid-state secondary battery can all be conventional materials in the art. For example, if it is a solid-state lithium secondary battery, the positive electrode material can be one of lithium iron phosphate, lithium cobalt oxide, lithium manganate, lithium nickel manganate, ternary nickel cobalt manganese, and ternary nickel cobalt aluminum. The negative electrode material can be one of a metal lithium sheet, graphite, hard carbon, soft carbon, silicon carbon, and lithium titanate. If it is a solid-state sodium secondary battery, the positive electrode material can be one of sodium vanadium phosphate, sodium vanadium fluorophosphate, sodium iron phosphate, sodium iron sulfate, sodium copper iron manganate, sodium nickel iron manganate, and a Prussian blue analog, and the negative electrode material can be one of a metal sodium sheet, a metal sodium alloy, hard carbon, soft carbon, and sodium titanate.
[0055] The solid-state secondary battery in the present invention has the advantages of the formed solid electrolyte, so that the solid-state battery has excellent cycle performance and coulombic efficiency.
[0056] The present invention is described below by means of specific examples. It should be noted that the following specific examples are only for illustrative purposes and do not limit the scope of the present invention in any way. In addition, unless otherwise specified, methods without specific conditions or steps are conventional methods, and the reagents and materials used can be obtained from commercial channels.
[0057] Example 1
[0058] This embodiment discloses a method for preparing a solid electrolyte and a solid battery by using ultrasonic in-situ polymerization, and the specific steps are as follows:
[0059] In an argon-protected glove box, polymerizable monomer ethoxylated trimethylolpropane triacrylate, sodium salt of sodium bistrifluoromethylsulfonyl imide, initiator azobisisobutyronitrile, and plasticizer additive propylene carbonate were mixed uniformly in a mass ratio of 65:14:1:20 to form a prepolymer precursor solution;
[0060] Take a glass fiber diaphragm, and drop 80 μl of the above prepolymer precursor solution on both sides of the glass fiber diaphragm to completely soak it;
[0061] The glass fiber separator soaked in the prepolymer precursor solution is placed between the positive electrode and the negative electrode. In an ultrasonically induced atmosphere, the polymerizable monomers in the prepolymer precursor solution are polymerized to form a solid electrolyte, and Na||Na 3 V 2 (PO 4 ) 3 Solid-state battery, wherein the ultrasonic-induced reaction temperature is 30°C, the ultrasonic frequency is 40kHz, the ultrasonic power is 500W, and the ultrasonic time is 12h.
[0062] After testing, the room temperature ionic conductivity of the solid electrolyte prepared in this embodiment is σ=8.2×10 -4 S cm -1 .
[0063] Comparative Example 1
[0064] This comparative example adopts the same implementation method as Example 1, except that the polymerization method adopts traditional thermal in-situ polymerization. The specific steps are as follows:
[0065] In an argon-protected glove box, polymerizable monomer ethoxylated trimethylolpropane triacrylate, sodium salt of sodium bistrifluoromethylsulfonyl imide, initiator azobisisobutyronitrile, and plasticizer additive propylene carbonate were mixed uniformly in a mass ratio of 65:14:1:20 to form a prepolymer precursor solution;
[0066] Take a glass fiber diaphragm, and drop 80 μl of the above prepolymer precursor solution on both sides of the glass fiber diaphragm to make it completely soaked;
[0067] The glass fiber separator soaked in the prepolymer precursor solution was placed between the positive electrode and the negative electrode and placed in a 60°C environment for 12 hours to allow the polymerizable monomers in the prepolymer precursor solution to fully polymerize to form a solid electrolyte. At the same time, Na||Na 3 V2 (PO 4 ) 3 Solid-state battery.
[0068] After testing, the room temperature ionic conductivity of the solid electrolyte prepared in this embodiment is σ=4.2×10 -4 S cm -1 .
[0069] At room temperature, the Na||Na 3 V 2 (PO 4 ) 3 Solid-state batteries undergo electrochemical performance testing.
[0070] Figure 2 The ultrasonic induced in-situ curing in Example 1 and the conventional heat induced in-situ curing process in Comparative Example 1 were used to assemble Na||Na 3 V 2 (PO 4 ) 3 Comparison of electrochemical impedance spectra of solid-state batteries. After testing, the interface impedance R ct is 920Ω, while the interface impedance R of the solid electrolyte prepared by ultrasonic induced in-situ solidification technology in Example 1 is ct As low as 450Ω, it can be concluded that the solid electrolyte prepared in Example 1 has lower interface impedance.
[0071] Figure 3 is the Na||Na prepared in Example 1 3 V 2 (PO 4 ) 3 Typical charge and discharge curve of solid-state battery at 25°C and 1C rate. Figure 4 The following are the cycle performance curve and Coulomb efficiency curve. Figure 3 and Figure 4 The test results show that the Na||Na 3 V 2 (PO 4 ) 3 After 100 cycles, the capacity retention rate of the solid-state battery reaches 98.9%, and the Coulomb efficiency is above 99.4%.
[0072] Example 2
[0073] This embodiment discloses a method for preparing a solid electrolyte and a solid battery by using ultrasonic in-situ polymerization, and the specific steps are as follows:
[0074] In an argon-protected glove box, a polymerizable monomer polyethylene glycol diacrylate, a lithium salt of lithium bis(fluorosulfonyl)imide, an initiator azobis(isoheptyl)nitrile, and a plasticizer additive fluoroethylene carbonate were mixed uniformly in a mass ratio of 48:10:2:40 to form a prepolymer precursor solution;
[0075] Take a polypropylene diaphragm and add 40 μl of prepolymer precursor solution on both sides of the polypropylene diaphragm to completely soak it;
[0076] The polypropylene separator soaked in the prepolymer precursor solution is placed between the positive electrode and the negative electrode. In an ultrasonically induced atmosphere, the polymerizable monomer is polymerized to form a solid electrolyte, and Li||LiFePO is obtained. 4 Solid-state battery, wherein the ultrasonic-induced reaction temperature is 20°C, the ultrasonic frequency is 60kHz, the ultrasonic power is 800W, and the ultrasonic time is 6h.
[0077] After testing, the room temperature ionic conductivity of the solid electrolyte prepared in this embodiment is σ=1.2×10 -3 S cm -1 .
[0078] Example 3
[0079] This embodiment discloses a method for preparing a solid electrolyte and a solid battery by using ultrasonic in-situ polymerization, and the specific steps are as follows:
[0080] In an argon-protected glove box, polymerizable monomer pentaerythritol tetraacrylate, lithium salt lithium hexafluorophosphate, initiator dibenzoyl peroxide, and plasticizer additive succinonitrile are mixed uniformly in a mass ratio of 20:15:1:64 to form a prepolymer precursor solution;
[0081] Take a polyethylene diaphragm and drip 40 μl of prepolymer precursor solution on both sides of the polyethylene diaphragm to completely soak it;
[0082] A polyethylene separator soaked in prepolymer precursor liquid is placed between the positive electrode and the negative electrode, and in an ultrasonically induced atmosphere, the polymerizable monomer is polymerized to form a solid electrolyte, and a silicon-carbon||NCM811 solid-state battery is obtained at the same time. The ultrasonically induced reaction temperature is 40°C, the ultrasonic frequency is 40kHz, the ultrasonic power is 500W, and the ultrasonic time is 12h.
[0083] After testing, the room temperature ionic conductivity of the solid electrolyte prepared in this embodiment is σ=7.8×10 -4 S cm -1 .
[0084] Example 4
[0085] This embodiment discloses a method for preparing a solid electrolyte and a solid battery by using ultrasonic in-situ polymerization, and the specific steps are as follows:
[0086] In an argon-protected glove box, polymerizable monomer methyl methacrylate, sodium salt sodium perchlorate, initiator cyclohexanone peroxide, and plasticizer additive lithium lanthanum zirconium oxide powder were mixed uniformly in a mass ratio of 65:12:3:20 to form a prepolymer precursor solution;
[0087] Take a glass fiber diaphragm and add 80 μl of prepolymer precursor solution to both sides of the glass fiber diaphragm to completely soak it;
[0088] The glass fiber separator soaked in the prepolymer precursor solution is placed between the positive electrode and the negative electrode. In an ultrasonically induced atmosphere, the polymerizable monomer is polymerized to form a solid electrolyte, and a hard carbon||Na 0.9 [Cu 0.22 Fe 0.3 Mn 0.48 ]O 2 Solid-state battery, wherein the ultrasonic-induced reaction temperature is 30°C, the ultrasonic frequency is 60kHz, the ultrasonic power is 1000W, and the ultrasonic time is 1h.
[0089] After testing, the room temperature ionic conductivity of the solid electrolyte prepared in this embodiment is σ=9.2×10 -4 S cm -1 .
[0090] Example 5
[0091] This embodiment discloses a method for preparing a solid electrolyte and a solid battery by using ultrasonic in-situ polymerization, and the specific steps are as follows:
[0092] In an argon-protected glove box, a polymerizable monomer, polyethylene glycol methyl ether methacrylate, sodium difluorooxalate borate sodium salt, an initiator, sodium trifluoromethane sulfonate, an additive, ethylene carbonate, and an additive, dimethyl carbonate, are mixed uniformly in a mass ratio of 29.5:10:0.5:30:30 to form a prepolymer precursor solution;
[0093] Take a glass fiber diaphragm and add 40 μl of prepolymer precursor solution on both sides of the glass fiber diaphragm to completely soak it;
[0094] The glass fiber separator soaked in the prepolymer precursor solution is placed between the positive electrode and the negative electrode. In an ultrasonically induced atmosphere, the polymerizable monomer is polymerized to form a solid electrolyte, and Na||NaFe(SO 4 ) 2 Solid-state battery, wherein the ultrasonic-induced reaction temperature is 50°C, the ultrasonic frequency is 20kHz, the ultrasonic power is 200W, and the ultrasonic time is 24h.
[0095] After testing, the room temperature ionic conductivity of the solid electrolyte prepared in this embodiment is σ=1.6×10 -3 S cm -1 .
[0096] Example 6
[0097] This embodiment discloses a method for preparing a solid electrolyte and a solid battery by using ultrasonic in-situ polymerization, and the specific steps are as follows:
[0098] In an argon-protected glove box, polymerizable monomer vinylene carbonate, sodium hexafluorophosphate sodium salt, and initiator methyl ethyl ketone peroxide were mixed uniformly in a mass ratio of 85:14:1 to form a prepolymer precursor solution;
[0099] Take a glass fiber diaphragm and add 80 μl of prepolymer precursor solution to both sides of the glass fiber diaphragm to completely soak it;
[0100] The glass fiber separator soaked in the prepolymer precursor solution is placed between the positive electrode and the negative electrode. In the ultrasonic induced atmosphere, the polymerizable monomer is polymerized to form a solid electrolyte, and Na||Na 3 V 2 (PO 4 ) 2 F 3 Solid-state battery, wherein the ultrasonic-induced reaction temperature is 30°C, the ultrasonic frequency is 50kHz, the ultrasonic power is 600W, and the ultrasonic time is 8h.
[0101] After testing, the room temperature ionic conductivity of the solid electrolyte prepared in this embodiment is σ=7.3×10 -4 S cm -1 .
[0102] Example 7
[0103] This embodiment discloses a method for preparing a solid electrolyte and a solid battery by using ultrasonic in-situ polymerization, and the specific steps are as follows:
[0104] In an argon-protected glove box, a polymerizable monomer, polyethylene glycol diglycidyl ether, a lithium salt, lithium bis(fluorosulfonyl)imide, an initiator, lauroyl peroxide, and a plasticizer additive, an ionic liquid PP13TFSI, were mixed uniformly in a mass ratio of 39.5:20:0.5:40 to form a prepolymer precursor solution;
[0105] Provide a glass fiber diaphragm, and drip 40 μl of prepolymer precursor solution on both sides of the glass fiber diaphragm to completely soak it;
[0106] A glass fiber separator soaked in prepolymer precursor liquid is placed between the positive electrode and the negative electrode, and in an ultrasonically induced atmosphere, the polymerizable monomer is polymerized to form a solid electrolyte, and a graphite||NCM811 solid-state battery is obtained at the same time. The ultrasonically induced reaction temperature is 40°C, the ultrasonic frequency is 30kHz, the ultrasonic power is 600W, and the ultrasonic time is 5h.
[0107] After testing, the room temperature ionic conductivity of the solid electrolyte prepared in this embodiment is σ=6.7×10 -4 S cm -1 .
[0108] Example 8
[0109] This embodiment discloses a method for preparing a solid electrolyte and a solid battery by using ultrasonic in-situ polymerization, and the specific steps are as follows:
[0110] In an argon-protected glove box, polymerizable monomer dipentaerythritol pentaacrylate, lithium salt lithium difluorooxalate borate, initiator azobisisobutyronitrile, plasticizer additive fluoroethylene carbonate and succinonitrile were mixed uniformly in a mass ratio of 30:12:1:30:27 to form a prepolymer precursor solution;
[0111] Take a polypropylene diaphragm and add 40 μl of prepolymer precursor solution on both sides of the polypropylene diaphragm to completely soak it;
[0112] A polypropylene separator soaked in prepolymer precursor liquid is placed between the positive electrode and the negative electrode, and in an ultrasonically induced atmosphere, the polymerizable monomer is polymerized to form a solid electrolyte, and a Li-In||NCM811 solid-state battery is obtained at the same time. The ultrasonically induced reaction temperature is 20°C, the ultrasonic frequency is 50kHz, the ultrasonic power is 400W, and the ultrasonic time is 12h.
[0113] After testing, the room temperature ionic conductivity of the solid electrolyte prepared in this embodiment is σ=2.3×10 -3 S cm -1 .
[0114] Example 9
[0115] This embodiment discloses a method for preparing a solid electrolyte and a solid battery by using ultrasonic in-situ polymerization, and the specific steps are as follows:
[0116] In an argon-protected glove box, a polymerizable monomer, polyethylene glycol methyl ether acrylate, a lithium salt, lithium hexafluorophosphate, an initiator, di-tert-butyl peroxide, a plasticizer additive, lithium lanthanum titanium oxide powder, and fluoroethylene carbonate were mixed uniformly in a mass ratio of 4:18:1:10:67 to form a prepolymer precursor solution;
[0117] Take a cellulose nonwoven membrane and drop 60 μl of prepolymer precursor solution on both sides of the cellulose nonwoven membrane to completely soak it;
[0118] The cellulose nonwoven membrane soaked in the prepolymer precursor solution is placed between the positive electrode and the negative electrode. In an ultrasonically induced atmosphere, the polymerizable monomers are polymerized to form a solid electrolyte, and Li||LiCoO is obtained. 2 Solid-state battery, wherein the ultrasonic-induced reaction temperature is 20°C, the ultrasonic frequency is 80kHz, the ultrasonic power is 100W, and the ultrasonic time is 24h.
[0119] After testing, the room temperature ionic conductivity of the solid electrolyte prepared in this embodiment is σ=8.1×10 -4 S cm -1 .
[0120] Table 1 Performance test results of solid electrolytes and solid batteries in Examples and Comparative Examples
[0121]
[0122] Table 1 shows the performance test results of the solid electrolytes and solid-state batteries prepared in Examples 1-9 and Comparative Example 1. It can be seen that the solid electrolyte prepared by the preparation method of the present invention has high room temperature ionic conductivity and low interface impedance, and the solid-state battery prepared in this way has excellent cycle performance and coulombic efficiency, indicating that the method of preparing electrolyte by ultrasonic induced in-situ polymerization and curing in the present invention has significant advantages and progress.
[0123] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0124] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a solid electrolyte, characterized in that: The following steps are involved: Providing a prepolymer precursor solution, wherein the prepolymer precursor solution contains a polymerizable monomer, an electrolyte salt and an initiator; Providing a porous support material so that it is completely infiltrated by the prepolymer precursor liquid; The impregnated porous support material is placed between the positive electrode sheet and the negative electrode sheet, and the polymerizable monomer is polymerized and solidified to form a solid electrolyte through ultrasonic induction.
2. The method for preparing a solid electrolyte according to claim 1, characterized in that: The polymerizable monomer is a free radical polymerizable monomer.
3. The method for preparing a solid electrolyte according to claim 2, characterized in that: The free radical polymerizable monomer is selected from at least one of methyl methacrylate, ethyl methacrylate, ethoxylated trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, glycidyl methacrylate, vinylene carbonate, and an oligomer monomer having a weight average molecular weight not exceeding 2000.
4. The method for preparing a solid electrolyte according to claim 3, characterized in that: The oligomer monomer is selected from at least one of polyethylene glycol acrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate and polyethylene glycol methyl ether acrylate.
5. The method for preparing a solid electrolyte according to claim 1, characterized in that: The electrolyte salt is a lithium salt or a sodium salt.
6. The method for preparing a solid electrolyte according to claim 5, characterized in that: The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorooxalatoborate, and lithium bis(oxalate)borate.
7. The method for preparing a solid electrolyte according to claim 5, characterized in that: The sodium salt is selected from at least one of sodium hexafluorophosphate, sodium tetrafluoroborate, sodium perchlorate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethylsulfonyl)imide, sodium trifluoromethanesulfonate, sodium difluorooxalatoborate, and sodium bis(oxalyl)borate.
8. The method for preparing a solid electrolyte according to any one of claims 1 or 5 to 7, characterized in that: The total molar concentration of the electrolyte salt in the prepolymer precursor solution is 0.5-4.0 mol / L.
9. The method for preparing a solid electrolyte according to claim 1, characterized in that: Based on the prepolymer precursor solution, the mass fraction of the initiator is 0.05-5wt%.
10. The method for preparing a solid electrolyte according to claim 9, characterized in that: The initiator comprises at least one of azobisisobutyronitrile, azobisisoheptylnitrile, dimethyl azobisisobutyrate, dibenzoyl peroxide, lauroyl peroxide, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, tert-butyl benzoyl peroxide, methyl ethyl ketone peroxide, cyclohexanone peroxide, di-tert-butyl peroxide, and diisopropylbenzene peroxide.
11. The method for preparing a solid electrolyte according to claim 1, characterized in that: The porous support material is selected from one or a combination of two or more of polyolefin membranes, ceramic-coated polyolefin membranes, PVDF-coated polyolefin membranes, polyimide membranes, polyethylene terephthalate membranes, cellulose nonwoven membranes, and glass fiber membranes.
12. The method for preparing a solid electrolyte according to claim 1, characterized in that: The prepolymer precursor solution also contains a plasticizer additive.
13. The method for preparing a solid electrolyte according to claim 12, characterized in that: The plasticizer additive is selected from at least one of fluoroethylene carbonate, ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, vinylene carbonate, succinonitrile, glutaronitrile, and inorganic solid electrolyte powder.
14. The method for preparing a solid electrolyte according to claim 12, characterized in that: Based on the prepolymer precursor solution, the mass fraction of the plasticizer additive is 0.5-80wt%.
15. The method for preparing a solid electrolyte according to claim 1, characterized in that: The reaction temperature of the ultrasonic induced polymerization is 20-50° C., the ultrasonic power is 100W-1000W, the ultrasonic frequency is 20kHz-80kHz, and the ultrasonic time is 0.5h-12h.
16. A solid electrolyte, characterized in that: The method is prepared according to any one of claims 1 to 15.
17. A solid-state secondary battery, characterized in that: Contains a solid electrolyte prepared by the preparation method according to any one of claims 1 to 15.
18. The solid-state secondary battery according to claim 17, characterized in that: The solid-state secondary battery is a solid-state lithium secondary battery or a solid-state sodium secondary battery.
19. The solid-state secondary battery according to claim 18, characterized in that: The solid-state lithium secondary battery is a lithium ion battery or a lithium metal battery.
20. The solid-state secondary battery according to claim 18, characterized in that: The solid-state sodium secondary battery is a sodium ion battery or a sodium metal battery.
